Мой Пушкин: [сборник] / М. И. Цветаева - Цветаева Марина Ивановна (Советский писатель, 1981)
Экземпляры: ф.11 (20190116) / Инвентарный номер: 06562 / Цена: 0.75 / Авт.знак: Ц 27 / ГРНТИ: 17.82.82 / ББК: 83.3(2Рос=Рус)1